Observation Interventions as a Means to Manipulate Collective Efficacy in Groups - Stephen Mellalieu (Journal of Sport and Exercise Psychology, 2014)
The purpose of this multistudy investigation was to examine observation as an intervention for the manipulation of individual collective efficacy beliefs. Study 1 compared the effects of positive, neutral, and negative video footage of practice trials from an obstacle course task on collective efficacy beliefs in assigned groups. The content of the observation intervention (i.e., positive, neutral, and negative video footage) significantly influenced the direction of change in collective efficacy (p < .05). Study 2 assessed the influence of content familiarity (own team/sport vs. unfamiliar team/sport) on individual collective efficacy perceptions when observing positive footage of competitive basketball performance. Collective efficacy significantly increased for both the familiar and unfamiliar conditions postintervention, with the largest increase for the familiar condition (p < .05). The studies support the use of observation as an intervention to enhance individual perceptions of collective efficacy in group-based activities. The findings suggest that observations of any group displaying positive group characteristics are likely to increase collective efficacy beliefs; however, observation of one’s own team leads to the greatest increases.